2021
DOI: 10.1039/d0sc06095j
|View full text |Cite
|
Sign up to set email alerts
|

Observation of liquid–liquid phase separation of ataxin-3 and quantitative evaluation of its concentration in a single droplet using Raman microscopy

Abstract: Liquid–liquid phase separation (LLPS) plays an important role in a variety of biological processes and is also associated with protein aggregation in neurodegenerative diseases. Quantification of LLPS is necessary to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 58 publications
1
59
2
Order By: Relevance
“…So far, LLPS is usually characterized in vitro by differential interference contrast (DIC) and/or fluorescence microscopy, fluorescence correlation spectroscopy 51 , turbidity, and absorption at 280 nm 52 . Microfluidic approaches 53 – 55 to characterize the phase diagram have also been proposed as well as NMR 56 , quantitative phase microscopy 57 and Raman microscopy/spectroscopy 58 , 59 techniques. However, easily approachable HTP methods for characterizing LLPS are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…So far, LLPS is usually characterized in vitro by differential interference contrast (DIC) and/or fluorescence microscopy, fluorescence correlation spectroscopy 51 , turbidity, and absorption at 280 nm 52 . Microfluidic approaches 53 – 55 to characterize the phase diagram have also been proposed as well as NMR 56 , quantitative phase microscopy 57 and Raman microscopy/spectroscopy 58 , 59 techniques. However, easily approachable HTP methods for characterizing LLPS are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A direct measurement of the concentration in the condensates using the 1 H- 15 N heteronuclear quantum coherence spectrum showed a much higher value of 27.7 mM for the RNA-binding protein FUS [ 10 ]. A similar concentration (around 14 mM) was obtained using Raman spectroscopy of condensates formed by ataxin-3, a protein that forms aggregates in the neurodegenerative Machado–Joseph disease [ 11 ]. The total protein concentration in the cells has been estimated to be around 2.5 mM [ 12 ].…”
Section: Introductionmentioning
confidence: 69%
“…At t 0 , the protein secondary structure inside the droplets is composed of 45% α-helical, 5% β-sheet, and 50% disordered conformation ( Table S2 ). Previous Raman studies on phase-separated proteins also have indicated the presence of disordered conformation for the low complexity domain of fused in sarcoma and ataxin-3 ( 17 , 18 ). Helical structure for TDP-43 CTD droplets has been previously reported ( 12 , 19 ); however, the Raman data indicate a greater helical content than would be expected for the short transient helix (<10%) characterized by NMR.…”
Section: Resultsmentioning
confidence: 97%